2021
DOI: 10.1007/s10853-021-06037-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in reinforced composite design for ionizing radiation shielding applications: a review

Abstract: This review explored recent developments in reinforced composite design and applications for improved radiation shielding and high percentage attenuation. Radiation energy moves as a wave. Thus unguarded exposure to high-energy radiation is inimical to the human tissue and the overall health standing of individuals which may result in cancer, tumour, skin burns and cardiovascular diseases. Radiation energy is conventionally contained using lead-based shields. However, recent literature has faulted the continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…MoS 2 @PNC have exhibited increased toughness, enhanced tribological attributes, improved thermal stability, and enhanced flame repression. On the other hand, a versatile range of PNC has been fabricated for multifunctional applications 64‐135 . With the advancement in nanotechnology, it is anticipated that innovations generable in the next generation of MoS 2 @PNC are blue chip.…”
Section: Discussionmentioning
confidence: 99%
“…MoS 2 @PNC have exhibited increased toughness, enhanced tribological attributes, improved thermal stability, and enhanced flame repression. On the other hand, a versatile range of PNC has been fabricated for multifunctional applications 64‐135 . With the advancement in nanotechnology, it is anticipated that innovations generable in the next generation of MoS 2 @PNC are blue chip.…”
Section: Discussionmentioning
confidence: 99%
“…We specifically explore the integration of LDPE in various formulations, leveraging its known attributes of flexibility, durability, and ease of processing. Studies have shown the development of lead-free polymers which demonstrate improved photon attenuation radiation shielding across various industries compared to traditional lead-based shields which pose toxicity and handling challenges [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the known toxic effects of lead and some problems arising from its weight, the search for new radiation shielding materials as an alternative to lead has gained momentum. Glasses [1][2][3], alloys [4][5][6], concretes [7][8][9], composites [10][11][12] and minerals [13,14] are included in the search new alternative products to lead. In addition to these, the choice of metallic glasses is a new alternative for use in this field, as their elements are adjustable up to a certain point.…”
Section: Introductionmentioning
confidence: 99%